PENGGUNAAN MEDIA GEOBOARD UNTUK MENINGKATKAN HASIL BELAJAR SISWA MATERI PERSEGI DAN PERSEGI PANJANG DI SD - Mokodompis, Regita Restilia; Husain, Rustam I; Aries, Nur Sakinah; Marshanawiah, Andi; Mahniar, Ade (SCIENCE : Jurnal Inovasi Pendidikan Matematika dan IPA, 2026)
This study aims to examine the effectiveness of using Geoboard media in improving the learning outcomes of fourth-grade students on the learning material of squares and rectangles. This study was motivated by the low mathematics learning outcomes caused by the limited variation of teaching methods and the lack of attractive learning media. The research method used was Classroom Action Research (CAR), which consists of four stages: planning, implementation, observation, and reflection. The subjects of the study were 19 fourth-grade students of SDN 03 Bulango Utara. The results of the study indicate that the use of Geoboard media significantly improved students’ learning outcomes. In the initial observation, only 30% of students achieved learning mastery. After the implementation of the actions, learning mastery increased to 47.37% in Cycle I and reached 84.21% in Cycle II. In addition, there was an improvement in both teacher and student activities, which increased from the “fairly good” category to the “very good” category. The use of Geoboard media not only enhanced students’ understanding of square and rectangle concepts but also increased their motivation, active participation, and independent learning. ABSTRAK Penelitian ini bertujuan untuk mengetahui efektivitas penggunaan media Geoboard dalam meningkatkan hasil belajar siswa kelas IV pada materi persegi dan persegi panjang. Penelitian ini dilatarbelakangi oleh rendahnya hasil belajar matematika siswa akibat kurang bervariasinya metode pembelajaran dan kurangnya media yang menarik. Metode penelitian yang digunakan adalah Penelitian Tindakan Kelas (PTK) yang terdiri dari tahap perencanaan, pelaksanaan, observasi, dan refleksi. Subjek penelitian adalah 19 siswa kelas IV SDN 03 Bulango Utara. Hasil penelitian menunjukkan bahwa penggunaan media Geoboard dapat meningkatkan hasil belajar siswa secara signifikan. Pada observasi awal, hanya 30% siswa yang mencapai ketuntasan belajar. Setelah tindakan dilakukan, hasil belajar meningkat menjadi 47,37% pada siklus I dan mencapai 84,21%pada siklus II. Selain itu, terjadi peningkatan pada aktivitas guru dan siswa yang sebelumnya berada pada kategori “cukup baik” menjadi “sangat baik”. Penggunaan media Geoboard tidak hanya meningkatkan pemahaman konsep luas persegi dan persegi panjang, tetapi juga meningkatkan motivasi, partisipasi aktif, dan kemandirian belajar siswa.